Acute inositol‐stabilized arginine silicate supplementation may elicit benefits on cognitive tasks. (31st December 2021) - Gills, Joshua L; Campitelli, Anthony; Jones, Megan; Paulson, Sally; McWilliams, Dalton L; Dale, Stephanie; Madero, Erica N; Myers, Jennifer Rae; Glenn, Jordan M; Gray, Michelle
Abstract: Background: Alzheimer's disease and related dementias exhibit similar pathologies such as decreases in cerebral blood circulation and aluminum accumulation leading to decreases in cognitive ability. Acute inositol‐stabilized arginine silicate (ASI) purportedly enhances cerebral blood flow and removes aluminum from the brain. Moreover, ASI supplementation demonstrated the ability to increase processing speed in young adults. While processing speed is important, ASI's ability to improve other domains of cognitive function remain unknown. Therefore, the purpose of this current investigation is to evaluate the acute effects of ASI supplementation in young healthy adults on various cognitive tasks. Method: Eight young adults participated in this randomized, double‐blind, placebo‐controlled crossover study. Each participant completed the Repeatable Battery for the Assessment of Neuropsychological Status before and after the supplement (placebo 8g of dextrose or 1.5g ASI and 8g of dextrose) was consumed. Paired samples t‐test were utilized to assess the differences between language (LAN), attention (ATT), and delayed memory (DM) in each supplement group. Percent differences were used to assess differences between supplement trials. Result: Paired samples t‐test showed a significant difference ( p < 0.05) for DM index scores in both supplement groups; statistical trends were noticed in LAN ( p = .05) and ATT ( p = .07) domains after ASI supplementation. ATT improved by 8% after ASI supplementation compared to 0% in the control group; additionally, LAN scores increased by ∼8% for both supplement groups. DM scores decreased in both trials pre to post examination; but the percent decrease was less in the ASI trial (8%) compared to the placebo trial (12%). Conclusion: Our preliminary results demonstrated no significant differences between placebo and ASI trials. However, a larger sample size could illustrate significant findings during language and attention tasks while supplementing with ASI. Further research is needed to determine ASIs effect on brain health and ability to improve cognition in healthy younger adults.